Prediksi Kebangkrutan dengan Z-Score - Kartikosari, Zulia; Puspita, Erna (Universitas Nusantara PGRI Kediri, 2020)
Stochastic Frontier Approach (SFA) is a technique of measuring the level of efficiency with a parametric Bankruptcy prediction is very important as a basis for decision making, both for companies, investors and creditors. So that the decisions taken do not lead to losses in the future. This study aims to analyze the potential for bankruptcy using the Altman Z-Score method at Food and Beverages companies listed on the IDX for the 2016-2018 period. The research approach is descriptive quantitative, with purposive sampling technique in determining the research sample. The data analysis technique is by calculating the ratio according to the Altman Z-Score model, calculating the Z-Score value, then classifying and analyzing the condition of the company based on the predetermined cut off point. The results showed that in 2016 the companies that were in the “bankruptcy” category were ALTO, BTEK, BUDI, TBLA; included in the